Diversity and Community Structure of Typhlocybinae in the Typical Karst Rocky Ecosystem, Southwest China - Jinqiu Wang; Jia Jiang; Yongkuan Chi; Di Su; Yuehua Song (Diversity, 2023)
In karst ecosystems, different geographic environmental conditions can lead to different lithospheric conditions, thus determining community composition and altering biotic interactions. Guizhou Province is a typical ecologically fragile karst area located in the South China Karst. To explore the relationship between biodiversity and environmental changes in different karst habitats, the community structure of typhlocybinae (Hemiptera, Auchenorrhyncha, and Cicadellidae) in three typical karst areas in Guizhou Province (the Zhenfeng–Huajiang Demonstration Zone, the Bijie Salaxi Demonstration Zone, and the Shibing Yuntai Mountain Nature Reserve) was analyzed. These areas are characterized by differences in terms of their geographic environment. For field investigations, typhlocybinae specimens were collected from five common leafhopper host plants—Juglans regia L., Rhus chinensis Mill., Prunus persica (L.) Batsch, Prunus salicina Lindl., and Debregeasia orientalis C.J. Chen—in the three study areas. A total of 4078 typhlocybinae specimens were captured, belonging to 6 tribes, 40 genera, and 121 species. Among them, Alnetoidia dujuanensis, Limassolla lingchuanensis, and Singapora shinshana were the dominant species. The numbers of typhlocybinae specimens from each region were as follows: Shibing, 2170 (53.2%); Bijie, 973 (23.9%); and Huajiang, 935 (22.9%). The number of leafhoppers collected in areas with serious rocky desertification was low, and the number increased with the increase in vegetation coverage. The order of the influence of environmental factors on the community structure of the leafhoppers in the three study areas was Huajiang > Bijie > Shibing. This order is consistent with the ranking of rocky desertification grades in the three study areas. The order based on the number of units at different taxonomic levels was as follows: Bijie (6 tribes, 32 genera, and 68 species) > Huajiang (6 tribes, 22 genera, and 58 species) > Shibing (5 tribes, 21 genera, and 48 species). The results show that environmental factors, such as climate and host plant leaf traits, had various effects on the characteristics and diversity of the leafhopper communities in different grades of rocky desertification areas. This study demonstrates that there are differences in species diversity in different grades of karst rocky desertification areas and provides a theoretical basis for future rocky desertification control and regional ecological restoration.